Desenvolvimento, caracterização e aplicação de lubrificantes modificados por nanoplacas de grafite - Flavio Antonio Cotta Vidal (2014)
This paper proposes a deeper knowledge of the mechanical wear using nanographite platelets dispersed in oil, since few research have been published using nanographite platelets dispersed in liquids, in order to evaluate its behavior in reducing the wear of mechanical components. It will be evaluated if the use of nanographite platelets shows a reduction of friction and wear advantages, and in which type and percentual concentration. To do this evaluation the selection of nanographite particles to be used in this work was done with the supply of local raw material, due to its wide availability in Brazil, which has a wealth of mineral graphite. Another important variable which will be discussed is the dispersion of nanographite, since this is a factor of crucial importance in order to establish a maximum performance of the nanoparticles in reducing wear. Furthermore, this paper also proposes the application of nanographite platelets dispersed in oil in automotive components. It was chosen to apply it to the internal components of the vehicle in order to study the effectiveness of the reduction of friction and mechanical wear by reducing noise generated inside the passenger compartment of the vehicle. The experimental results showed that nanographite platelets dispersed in oil reduced friction and wear, and when applied on the door latch of the vehicle reduce the his interior noise. Therefore the aim of this work is the development of a new product with national technology, which has characteristics of ideal performance for reducing noise in the vehicle. This study will address nanomaterials, specially nanographite platelets, and their forms of characterization, concepts and tribological tests of friction and wear, in addition to the attributes of acoustics and sound perception in closed environments such as the inside of the car, as well as vehicle performance.